2014
DOI: 10.1002/pbc.25011
|View full text |Cite
|
Sign up to set email alerts
|

Focused screening of a panel of cancer‐related genetic polymorphisms reveals new susceptibility loci for pediatric acute lymphoblastic leukemia

Abstract: These findings reveal two independent novel susceptibility loci for childhood ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The heritable basis of susceptibility to ALL is further supported by recent candidate gene and genome-wide association studies (GWAS), suggesting that co-inheritance of multiple germline variants may contribute to the risk of the disease. Five GWAS have been performed with populations of 3 275 ALL cases and 4 817 healthy control individuals [ 8 ]. Four independent loci have been shown conclusively to be associated with ALL, and more specifically the B-cell precursor (BCP) ALL risk was associated with the particular SNPs located in 7p12.2 ( IKZF1 ), 9p12 ( CDKN2A/CDKN2B ), 10q21.2 ( ARID5B ) and 14q11.2 ( CEBPE ).…”
Section: Introductionmentioning
confidence: 99%
“…The heritable basis of susceptibility to ALL is further supported by recent candidate gene and genome-wide association studies (GWAS), suggesting that co-inheritance of multiple germline variants may contribute to the risk of the disease. Five GWAS have been performed with populations of 3 275 ALL cases and 4 817 healthy control individuals [ 8 ]. Four independent loci have been shown conclusively to be associated with ALL, and more specifically the B-cell precursor (BCP) ALL risk was associated with the particular SNPs located in 7p12.2 ( IKZF1 ), 9p12 ( CDKN2A/CDKN2B ), 10q21.2 ( ARID5B ) and 14q11.2 ( CEBPE ).…”
Section: Introductionmentioning
confidence: 99%
“…The heritable susceptibility to ALL is proven by the finding of recent candidate-gene and genome-wide association studies (GWAS). Some authors suggested that ALL risk is associated with multiple germline variants [12]; others disprove these hypotheses suggesting that the genetic susceptibility to ALL is mediated by a small number of genes with a strong effect rather than the cumulative effect of small genes [13]. In fact, the first GWAS performed by Trevino and colleagues, identified eighteen germline single nucleotide polymorphisms (SNPs) of 307,944 subjects with allele frequencies are higher in pediatric ALL population that in non-ALL controls ( p < 1 × 10–5) [9].…”
Section: Introductionmentioning
confidence: 99%